2020
DOI: 10.1080/1059924x.2020.1814920
|View full text |Cite
|
Sign up to set email alerts
|

Essential and Vulnerable: Implications of Covid-19 for Farmers in Ireland

Abstract: Objectives: This paper seeks to: provide an overview of the impacts of and responses to the spread of COVID-19 in Ireland; assess the vulnerability of the population living in rural areas to COVID-19; compare the health status of male farmers to underlying medical conditions frequently associated with those experiencing the worst impacts of the illness; and assess the implications of COVID-19 for farmers living alone and farm households with children. Methods: We present an overview of the impact and response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 2 publications
(2 reference statements)
1
19
0
2
Order By: Relevance
“…No study mentioned unemployment as an exposure factor in South America, whilst one study each identified unemployment as an exposure in North America (Peters 2020 ), Australia (Kent et al 2020 ) and Europe (De Luca, Tondelli & Åberg 2020 ). Socio-economic marginalisation was reported in six studies (Alvi & Gupta 2020 ; Dube 2020 ; Henning-Smith 2020 ; Haynes-Maslow et al 2020 ; Peters 2020 ; Surendra 2020 ) and remoteness of rural areas in four studies (Ali et al 2020 ; Haynes-Maslow et al 2020 ; Henning-Smith 2020 ; Meredith et al 2020 ). Malnutrition (Cattivelli & Rusciano 2020 ; Francis & Pegg 2020 ) and insecurity (Cattivelli & Rusciano 2020 ; Francis & Pegg 2020 ) were reported in two studies each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No study mentioned unemployment as an exposure factor in South America, whilst one study each identified unemployment as an exposure in North America (Peters 2020 ), Australia (Kent et al 2020 ) and Europe (De Luca, Tondelli & Åberg 2020 ). Socio-economic marginalisation was reported in six studies (Alvi & Gupta 2020 ; Dube 2020 ; Henning-Smith 2020 ; Haynes-Maslow et al 2020 ; Peters 2020 ; Surendra 2020 ) and remoteness of rural areas in four studies (Ali et al 2020 ; Haynes-Maslow et al 2020 ; Henning-Smith 2020 ; Meredith et al 2020 ). Malnutrition (Cattivelli & Rusciano 2020 ; Francis & Pegg 2020 ) and insecurity (Cattivelli & Rusciano 2020 ; Francis & Pegg 2020 ) were reported in two studies each.…”
Section: Resultsmentioning
confidence: 99%
“…† Numbers in parentheses is the total number from each country Maslow et al 2020;Peters 2020;Surendra 2020(Ali et al 2020;Haynes-Maslow et al 2020;Henning-Smith 2020;Meredith et al 2020). Malnutrition(Cattivelli & Rusciano 2020;Francis & Pegg 2020) and insecurity(Cattivelli & Rusciano 2020;Francis & Pegg 2020) were reported in two studies each.…”
mentioning
confidence: 99%
“…24 O aumento da vulnerabilidade socioeconômica desses trabalhadores pode acarretar implicações sociais negativas, principalmente relacionados à saúde física e mental, como evidenciado no artigo A4. 16 Diante disso, é importante reavaliar as medidas públicas que concedem mais de 70% do crédito para o financiamento da produção rural à agricultura patronal, direcionada à produção de commodities. Faz-se necessário voltar o olhar para a agricultura familiar, que é melhor distribuída geograficamente que possibilita o abastecimento local, uma vez que produz alimentos diversificados) e ocupa mais de 80% dos trabalhadores rurais com uso de práticas produtivas mais sustentáveis.…”
Section: Discussionunclassified
“…21 Em cenários de crise como o que o mundo inteiro está vivenciando, o agronegócio, dentre outros setores, mostra-se produtivo, dado que a agricultura tem sido responsável por contínuos superavit comerciais, os quais são significativos para manutenção das condições externas do país e principalmente diante da desaceleração da atividade interna. 26 Em contrapartida, o trabalho A4 16 destaca que a classificação dos agricultores como essenciais significa que eles não podem "se dar ao luxo" do distanciamento social, colocando a si próprios e suas famílias em maior risco de exposição ao vírus da COVID-19. Algumas famílias agrícolas, particularmente aquelas que vivem sozinhas ou famílias com crianças pequenas, também são suscetíveis a impactos adversos em seu bem-estar, respectivamente associados ao distanciamento e severas restrições de tempo.…”
Section: Discussionunclassified
“…3 Salzwedel et al 4 remind us how critical childcare is, especially for those in agriculture where children are more at risk for injury and death than many industries combined. Similarly, the needs of single farmers as rural and isolated are brought to our attention through the work of Meredith et al 5 Here, the "luxury" of isolation in Irish farming is born truer as problematic as they continue essential work. In this regard, we are also forced to reckon with lesser known farm communities by Wypler and Hoffemeyer, 6 and that even within the agricultural community there are those more isolated than others.…”
Section: Crises Make the Vulnerable More Somentioning
confidence: 99%